The Orthopaedic Burden of Gun-shot Injury in Children: A Single-Institution Analysis - Devin A. Maez, BA; Samuel L. Flesner, BS; Angela M. Martz, PA-C; Patrick P. Bosch, MD; Richard J. Miskimins, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: The rates of firearm injuries among pediatric patients have risen significantly in recent years. Extremity injuries resulting from gunshot wounds (GSWs) often require orthopaedic management. In addition to rare nationwide database studies, there are 2 regional studies examining this trend in the South only. Our state has notably high gun ownership and lenient gun protection laws. To examine the orthopaedic burden of gunshot injuries in our region, we reviewed the pediatric patients presenting with GSWs at a tertiary level-1 trauma center over a 7-year period. Methods: A retrospective chart review was conducted of pediatric patients <18 years of age presenting with GSW-related injuries at our state's only level-1 trauma center from 2016 through 2022. Data collected included demographics, injury characteristics, fracture locations, surgical management, antibiotic treatment, and long-term complications. Statistical analysis was performed to identify significant trends and disparities. Results: GSW-related presentations increased 109% from 2016 to 2022 (P ​= ​.005), while orthopaedic consults increased 83% (P ​= ​.032), and GSW-related fractures increased 280% (P ​= ​.009). A total of 46.4% of all patients required orthopaedic consultation.Most patients were male (80.2%), with a mean age of 14.6 years (range: 16 months-17 years). Hispanic patients were over-represented compared to the state population (64.1% versus 47.7%, P ​< ​.001), as were African Americans (6.1% versus 1.8%, P ​< ​.001).A total of 4.8% of patients were uninsured. Privately insured individuals were under-represented (16.9% versus 35.9%, P ​< ​.001), whereas publicly insured patients were over-represented (78.2% versus 56.5%, P ​< ​.001). As per chart documentation, accidental discharge was the most common cause of injury (56.5%), followed by assault (33.9%).The overall fracture rate was 43.1%. Long-bone fractures accounted for 50.5% of all fractures. A total of 57.4% of orthopaedic consults required operative management. Documented antibiotic administration was noted in 84.4% of patients, predominantly cefazolin. Complications were observed in 36.5% of orthopaedic consults, with nerve injury being the most frequent (17.4%). Only 5.2% experienced infections. Conclusions: Pediatric GSW-related injuries in our state present a significant orthopaedic burden, with increasing trends in presentations and ballistic fractures over the study period. Orthopaedic surgeons have a significant role in managing these patients, improving treatment protocols and providing guidance for evidence-based approaches to improve laws to protect children. Key Concepts: (1) The study analyzes a 7-year trend of pediatric gunshot wound (GSW) presentations at our state's only level-1 trauma center, focusing on those requiring orthopaedic consultation. (2) Findings indicate a statistically significant increase in pediatric GSW-related presentations and orthopaedic consultations, highlighting an escalating clinical burden on orthopaedic services in this community. (3) Demographic analysis reveals overrepresentation of Hispanic and African American patients and a high prevalence of publicly insured individuals among pediatric GSW cases at this institution. (4) This research underscores the high rate of fractures and complications associated with pediatric GSWs, emphasizing the critical role of orthopaedic management. (5) The study provides valuable data on the epidemiology and significant orthopaedic burden of managing pediatric GSWs, with broader implications for improving treatment strategies and public health policies. Level of Evidence: III (Retrospective Cohort Study)